Novel insights into multitargeted potential of N′-(4-benzylpiperidin-1-yl)alkylamine derivatives in the management of Alzheimer's disease associated pathogenesis. Issue 106 (2nd November 2016) - Meena, Poonam; Manral, Apra; Nemaysh, Vishal; Saini, Vikas; Siraj, Fouzia; Luthra, Pratibha Mehta; Tiwari, Manisha
Abstract : In this work we investigate some of the key mechanisms behind the multitargeted potential of N′ -(4-benzylpiperidin-1-yl)alkylamine derivatives and their characterization for anti-Alzheimer effects. Abstract : In response to the molecular complexity of AD, the strategy of multi-target directed ligand (MTDL) holds great potential in modulating different targets involved in the neurodegenerative cascade of AD. In this context, there is a need for the use of privileged scaffolds for discovering potential multifunctional agents for AD treatment. Our group have previously reported a novel series of benzyl piperazine/piperidine based multifunctional agents endowed with in vitro profile appropriate for identifying novel lead candidates with disease-modifying potential. Herein, we have further made an attempt to decipher some of the key mechanisms behind the multitargeted potential of most active inhibitors (5h and5k ) and their characterization for anti-Alzheimer effects. In the present study, investigation of compounds5h and5k through CD experiments confirmed their ability in preventing β-sheet aggregation and fibril formation. Morphological visualization in TEM suggested that test inhibitors may interfere with rate of peptide nucleation, leading to short fibrillar aggregates. ThT based fluorimetric assay further demonstrated that5h and5k inhibited AChE-mediated Aβ fibrillogenesis via their interaction with the AChE peripheral anionic site. Molecular docking and simulations studies indicated that these compounds could potentially bind to Aβ by inhibiting the toxic conformation of Aβ1–42 and stabilizing the α-helical content. Furthermore, compounds exerted neuroprotective action on SH-SY5Y cells towards Aβ and H2 O2 -mediated cell death and oxidative injury by inhibiting ROS generation. Moreover, administration of5h and5k (5 mg kg −1 ), significantly reversed scopolamine-induced neurobehavioral, biochemical, neurochemical and histopathological changes in a manner comparable to standard drug donepezil. Together, the present findings provide novel insights into disease-modifying potential of benzylpiperidine derivatives towards the management of AD.